Effects of different doses of dezocine on central nervous system in mice - GONG,Wen-yi (2022)
Abstract Dezocine is an opioid receptor agonist – antagonist gaining popularity in clinical practice. It is both μ-receptor agonist and antagonist activities. This study was designed to investigate the effects of dezocine on the CNS oxidative and inflammation in mice. Eight-week old female BALB/c mice were obtained from Shanghai General Hospital of Nanjing Medical University animal center. All animal procedures were approved by the Animal Care and Use Committee of Nanjing Medical University. We found that increasing dose of dezocine induced oxidative stress and inflammation in multiple brain regions, including the prefrontal cortex, cerebellum, temporal cortex, and striatum. Elevated expression levels of anti- oxidants (NRF2, SOD-1 and HO-1), KEAP-1, GSH and MDA were found in the prefrontal cortex and striatum. Elevated HO-1 and NRF2 levels were detected in the cerebellum and temporal cortex in the 3.0 mg/kg dezocine treated group. The SOD-1, HO-1, KEAP-1, NRF2, GSH and MDA levels were similar among groups in the olfactory bulb. The prefrontal cortex and striatum showed the most elevated oxidative stress (NRF2, SOD-1, and HO-1) marker levels. The number of PV-positive interneurons was decreased in the 1.5 mg/kg dezocine treated group, while the number of PNNs steadily increased over 3.0 mg/kg dezocine treated.